Late Strunian age : a key time frame for VMS deposit exploration in the Iberian Pyrite Belt - Matos, João Xavier (2011)
Estimate of geological environments favorable for the formation of massive sulphide deposits is an important goal to the exploration companies working in the Iberian Pyrite Belt (IPB), the main European VMS base metals province, with giant deposits such as Neves Corvo, Aljustrel (Portugal), Rio Tinto and Tharsis (Spain). Palynostratigraphic research programs using more than 40 exploration boreholes (>30 km length) allowed the dating of the sediments of the Volcano-Sedimentary Complex (upper Devonian to upper Viséan), that host the massive sulphide deposits. Research is based on detailed palynomorphs study. Careful work was focused on dark grey and black shale units that host stockwork and massive ore mineralizations. Felsic volcanic U/Pb age data was also used to confirm the sediment age.Late Strunian (miospore biozone LN, 360.7 ± 0.7 Ma -362 Ma) sediments host the massive sulphide ore at Neves Corvo, Lousal, Caveira and Montinho, mines located in the Portuguese IPB sector. In Spain similar data was obtained at Aznalcollar and Tharsis. The agedata show a favourable geological period of ~2 Ma were paleogeographic conditions were extremely favorable to hydrothermal fluid circulation and VMS deposits formation. Late Strunian age therefore becomes one key exploration guide in IPB.